A autonomia docente na (re)construção do currículo no cotidiano escolar - Schiabel, Daniela (2017)
This work analyses how it is set the teacher‟s autonomy in school curriculum (re)building process, in Elementary school, from a school in the city of Paraguaçu-MG, that comes from the legislative sphere to the teaching practice and classroom. Therefore, it becomes necessary identifying how legal files present responsibility and the teacher‟s autonomy in what involves the curriculum development; as well understanding the way this autonomy is set in the educational institution advises; and in what level teachers present themselves as autonomous beings in this curriculum process. This study is based in the curriculum conception as project and in understanding the active teacher role that is established in possibility and/or autonomy, that one has to, in one‟s classroom, transforms the predetermined curriculum in building knowledge moments and learning more significant to oneself and one‟s students. It is utilized as theoretical background authors such: Gimenio Sacristán; Tomaz Tadeu da Silva; Maria do Céu Roldão; José Augusto Pacheco; Michael Young; among others. This work is backed by qualitative research assumptions focusing in constructive interpretation. In such, we have used as base data collecting tool the legal documents analysis those legitimate the teaching autonomy; the participant observation in pedagogical meetings in the educational institution for six months and semi-structured interviews with seven teachers from elementary school. From the construction of the nuclei of signification it was possible the analysis and the data interpretation, It is possible stated that the Brazilian legislation assures the teacher‟s participation and autonomy in the school routine (re)building curriculum process, as in the institutional global aspect as in pedagogical acting developed in class. However, it is possible to spot teacher autonomy limitation attempts, mainly when the official curriculum is taken without proper context; the same way, it‟s verified that teachers, in their classroom, bearing in mind their students‟ learning process. So, it concludes that the autonomy exercise in school curriculum (re)building was composed in a strength and power game between legal, administrative and pedagogical spheres, which teachers project their professional autonomy possibilities and model the original project through planning and executing activities.